GEOMATE PROJECT : Implementation of Project Based Learning (PjBL) with STEAM approach in producing geometry transformations totebags as fashion products - Sizillia Noranda Mayangsari (CV. Gerasi Insan Nusantara, 2026)
This study aims to describe the implementation of the